PENDAMPINGAN PELAKSANAAN BIMBINGAN DAN KONSELING DI ERA NEW NORMAL DI SMPN 2 SAMBAS - Patriana Patriana (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
The government has issued regulations regarding efforts to prevent the spread of covid -19 pandemic in Indonesia. One of them is by imposing new normal behavior. Educators and student must be able to adapt to these changes so that the learning process goes well. The purpose of community service activities is to provide assistance in the implementation of guidance and counseling in the new normal era for counseling teachers at SMPN 2 Sambas. The implementation method is in the form of socialization and discussion. The result of the service activities found that activities that had been carried out ran smoothly and this activity also provides understanding to teachers about the implementation of guidance and counseling by making digital leaflets, online guidance boards, online problem boxs, home visit and cyber counseling.